Babuta'an Traditional Games In Increasing Students' Learning Motivation - Annisa Hasanah; Zain Ahmad Fauzi; Fahri Fajrul Falah; Norma Paulina; Asyfa Nabila; Linda Rosydah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The researcher chose the traditional game Bubuta'an to overcome noise outside the classroom due to school renovations which resulted in students' lack of focus on learning. The traditional game Bubuta'an is also a traditional game in South Kalimantan which in Indonesian is known as the game Si Buta-Si Buta. The aim of the research is to analyze the role of traditional babuta'an games in increasing students' learning motivation. The type of research used is Classroom Action Research with a qualitative approach. The research results show that the percentage of students' classical learning motivation obtained at the first meeting was 75% with the criterion